Effects of Streptomyces melanosporofaciens X216 on microbial diversity in oilseed rape soil - Liang, Hai-di; Zhou, Hu; Zhao, Hui; Ding, Lin; Zhou, Jia; Zhang, Ying-jun; Gao, Yang; Ren, Zuo-hua (Frontiers in Plant Science, 2024)
Introduction Clubroot disease is a devastating soil borne disease caused by infection with Plasmodiophora brassicae, which primarily affects cruciferous plants. The microbial diversity of the soil is an essential indicator of its quality. Methods This study measured the physicochemical properties of the soil to study the effect of its microbial diversity on the infection of oilseed rape with P. brassicae. High-throughput sequences of the soil bacteria and fungi in the inter-root soils of P. brassicae were analyzed under different treatment conditions. Results In the study, it was found that the efficiency of strain X216 in preventing and controlling the root disease of rapeseed was positively correlated with the amount of solution used to irrigate the root system. The results of the greenhouse and field trials showed that the efficiency of strain X216 against the root disease of rapeseed was 43.16% in the field and 62.14% in the greenhouse. Proteobacteria, Chloroflexi, Rozellomycota, and Basidiomycota are critical phylum in the development of clubroot disease. The application of biocontrol increased the relative abundance of Actinobacteria, Bacillus, Mesorhizobium, Mycobacterium, Streptomyces and Filobasidium, which affected the structure and abundance of microbial communities. A principal coordinate analysis showed that the microbial structure in the soil varied substantially in the bacterial community, and there was no significant difference in soil structure in the fungal community. Discussion The occurrence of clubroot disease affected the structure of inter-root microbial community composition in the soil, which resulted in a decrease in its community diversity. The application of the biocontrol bacterium X216 increased the soil microbial diversity. It effectively reduced the occurrence of P. brassicae, and this study provides a basis to study the microbial diversity in cruciferous crops.